Hypertension Clinic Service is a Good Opportunity for Tobacco Cessation in Bangladeshi Villagers (Cardiovascular Journal, 2016)
Background: Tobacco use and hypertension are common and co-existent in Bangladeshi population. This study was done to assess whether a brief counseling by non-medical counselors during checkup visits for hypertension treatment can reduce tobacco use in Bangladeshi adults living in a village.Methods: This study was done in a public health clinic located in a village of Bangladesh. Consecutive 259 hypertensive patients visiting this clinic for hypertension treatment were counseled for lifestyle modification at entry and four follow-up visits at an interval of four weeks. Tobacco users were counseled for five minutes to quit tobacco use at each visit as per a cessation booklet in Bangla. Data on tobacco use, smoking and smokeless, were recorded at all visits.Results: Median age of the respondents was 55 years (in range, 18- 85 years) and three-quarter of them were women. The prevalence of tobacco use in first visit was 40.5% which declined to 1.9% on their fifth visit. Major decline was observed due to smokeless tobacco quitting; its prevalence dropped from 33.2% to 0.4%. However smoking was relatively resistant; it declined from 10.4% to 1.5% only.Conclusion: Tobacco cessation by a simple counseling has been found to be very successful in this village level public health clinic of Bangladesh. This can be replicated in similar settings such as community clinics.Cardiovasc. j. 2016; 9(1): 19-22